Penyerapan Tenaga Kerja: Pendekatan Panel Least Square (PLS) di Pulau Jawa-Bali Tahun 2012-2022 - Moch Syamsudin (Diponegoro Journal of Economics, 2024)
Human resources are the most important factor in managing the available natural resources. Population growth from time to time can be a driving or inhibiting factor in economic growth. A process of economic development cannot be separated from population growth. This is related to resources that support economic development, in which human resources are the most important aspect of development besides natural resources, capital/technology, and social politics. This research aims to see the effect of education, minimum wages, investment, and economic growth on employment in Java and Bali in 2012-2022. The method used is Panel Least Square (PLS). The results show that education and minimum wages have an insignificant effect on employment. Investment and economic growth have a significant and positive effect on employment. The implementation of wages for workers needs to be reviewed so that the wages received can provide peace in living life. The increase in the minimum wage must be able to be collaborated with always learning and increasing capabilities for the needs of the world of work. Government policies in maintaining the momentum of economic growth after the COVID-19 pandemic by accelerating national economic recovery need to be increased. Carrying out realization and working with foreign countries in bringing in investment is needed so that the absorption of labor is higher.